PENGARUH MINAT BERWIRAUSAHA MAHASISWA TERHADAP PERTUMBUHAN EKONOMI DI SEKITAR UNIVERSITAS NEGERI SEMARANG: Universitas Negeri Semarang - Nabila Suci Oktafiana (Jurnal Ekonomi Bisnis Manajemen dan Akuntansi (JEBISMA), 2024)
Entrepreneurship is one of the employment opportunities that is indispensable for welcoming the country in the economic aspect. the country in the economic aspect. Entrepreneurship can reduce unemployment and poverty and increase employment and economic growth. Interest entrepreneurship is certainly the first bridge for business actors to become successful entrepreneurs. successful entrepreneur. Effective entrepreneurs are of course played by the younger generation, because their ideas and innovations are needed to become agents of change in improving the country's economy. change in improving the country's economy. This research uses quantitative approach method and descriptive research form. In this article this article examines the level of interest in entrepreneurship in UNNES students, as well as solutions to entrepreneurial obstacles to entrepreneurship faced by students.